Superior Treg-Expanding Properties of a Novel Dual-Acting Cytokine Fusion Protein - Padutsch, Tanja; Sendetski, Maksim; Huber, Carina; Peters, Nathalie; Pfizenmaier, Klaus; Bethea, John R.; Kontermann, Roland E.; Fischer, Roman (Frontiers in Pharmacology, 2019)
Autoimmune diseases are caused by uncontrolled endogenous immune responses against healthy cells. They may develop due to an impaired function of regulatory T cells (Tregs), which normally suppress self-specific effector immune cells. Interleukin 2 (IL-2) and tumor necrosis factor (TNF) have been identified as key players that promote expansion, function and stability of Tregs. In vivo, both low-dose IL-2 therapy and TNF receptor 2 (TNFR2) agonism were shown to expand Tregs and alleviate autoimmunity. We here designed a novel dimeric dual-acting fusion cytokine, where mouse IL-2 is genetically linked to a TNFR2-selective single-chain TNF mutein (IL2-EHD2-sc-mTNFR2). IL2-EHD2-sc-mTNFR2 showed high affinity to TNFR2 and efficiently activated IL-2 and TNFR2-selective signaling pathways. Further, IL2-EHD2-sc-mTNFR2 promoted superior Treg expansion, with both the IL-2 and the TNFR2 agonist (sc-mTNFR2) component necessary for this biological response. Ultimately, we propose that IL2-EHD2-sc-mTNFR2 is a dual-acting cytokine that efficiently promotes Treg expansion and might have a superior therapeutic window than conventional IL-2-based drugs.